2013
DOI: 10.3390/ijerph10010390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Duration of Exposure to Cement Dust on Respiratory Function of Non-Smoking Cement Mill Workers

Abstract: This study aimed to determine the effect of long term exposure to cement dust on lung function in non-smoking cement mill workers. This is a cross-sectional study of respiratory functions. Spirometry was performed in 100 apparently healthy volunteers; 50 non-smoking cement mill workers and 50 non-smoking un-exposed subjects. Based on the duration of exposure, cement mill workers were divided into three groups, less than 5, 5–10 and greater than 10 years. All subjects were individually matched for age, height, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 14 publications
5
45
0
Order By: Relevance
“…Similar observations have been reported by other studies [15, 16, 19, 20]. Bioaccumulation of some specific components as chromium and silica present in the cement dust in the respiratory tract may lead to delayed hypersensitivity reaction and chronic inflammation and hence impaired respiratory function.…”
Section: Discussionsupporting
confidence: 89%
“…Similar observations have been reported by other studies [15, 16, 19, 20]. Bioaccumulation of some specific components as chromium and silica present in the cement dust in the respiratory tract may lead to delayed hypersensitivity reaction and chronic inflammation and hence impaired respiratory function.…”
Section: Discussionsupporting
confidence: 89%
“…This assumption could be supported by the results of Olerue's [26] and Meo's et al [27] study. Olerue conducted a case-control study and reported that the lung function parameters FVC and FEV 1 were decreased with the duration of employment in cement industry [27].…”
Section: Resultssupporting
confidence: 80%
“…Olerue conducted a case-control study and reported that the lung function parameters FVC and FEV 1 were decreased with the duration of employment in cement industry [27]. Meo and his colleagues compared some spirometric indices in 50 non-smoking cement mill workers with 50 non-smoking un-exposed subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Also other studies concerned with these factors among workers of other types of industries such as Wood and oil industries and found similar findings (Assessment, 2011;Jerie, 2012;Meo et al, 2013, Eyayo, 2014. The safety measure and equipment are important factor for the safety and the protection of the workers in different workplaces the present study found that majority of the worker used protective clothing head protection equipment; hand and feet's protection equipment; on the other hand; about three quarters of the studied group used the respiratory equipment, these findings agreed that reported in Bangladeshi and Egyptian studies and these findings consistent with the legislations of occupational safety applied in these factories (Iqbal et al, 2010, Shafik & El-Mohsen, 2012).…”
Section: Chemical Factorssupporting
confidence: 67%
“…One of the main reasons for increased occupational hazards level is the costs of care and the lack of commitment by the private sectors in addressing environmental policy and therefore workers exposed to occupational hazards and failure to provide for that slide care (private industry) and the failure to provide health insurance for the class labor by the government and with the piece increases injury rate among workers of this side and the other hand must coordinate with the industrial government to work to reduce the risks and increase the proportion of occupational safety and health (Erhabor et al, 2013;Meo, Al-Drees et al, 2013). To ensure the well-being of more workers because it represents important segment on the level of industry and social he is human part of life must provide psychosocial support through the equivalent or through training courses on how hazard assessment and increased health awareness to prevent injuries and to improve worker health and increasing trends, skills and knowledge of those risks and thus serve the interests productivity and health, a goal of global safety for the workers organization (Cherrie et al, 2011) …”
Section: According To World Health Organization (Who)mentioning
confidence: 99%